2021
DOI: 10.1177/01945998211044683
|View full text |Cite
|
Sign up to set email alerts
|

Management of Flap Failure After Head and Neck Reconstruction: A Systematic Review and Meta‐analysis

Abstract: Objective To systematically review management of flap loss in head and neck construction with free tissue transfer as compared with locoregional flap or conservative management. Data Sources Medline, Embase, Scopus, Cochrane Central Register of Controlled Trials, Cochrane Database of Systematic Reviews, and ClinicalTrials.gov were searched up to October 2019. Review Methods Candidate articles were independently reviewed by 2 authors. Articles were considered eligible if they included adequate reporting of flap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…25 A recent meta-analysis indicated that a second free flap produced fewer perioperative complications when compared with locoregional alternatives in patients with previous free flap loss (relative risk, 0.6; 95% CI, 0.40 to 0.92; P = 0.02). 3 Remarkably, our findings indicated a higher flap success rate implementing locoregional flaps as a secondary reconstruction with a 90.9% success rate. In this setting, locoregional reconstructive options may be a valuable alternative when the wound bed is compromised or when, regardless of the physiologic status, patients need to undergo surgery because coverage is urgently required.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…25 A recent meta-analysis indicated that a second free flap produced fewer perioperative complications when compared with locoregional alternatives in patients with previous free flap loss (relative risk, 0.6; 95% CI, 0.40 to 0.92; P = 0.02). 3 Remarkably, our findings indicated a higher flap success rate implementing locoregional flaps as a secondary reconstruction with a 90.9% success rate. In this setting, locoregional reconstructive options may be a valuable alternative when the wound bed is compromised or when, regardless of the physiologic status, patients need to undergo surgery because coverage is urgently required.…”
Section: Discussionsupporting
confidence: 50%
“…Although a previous meta-analysis showed a 93% success rate for a secondary free flap (95% CI, 89% to 97%), outcomes throughout the literature are highly heterogeneous. 3 The rate for reconstruction salvage with a second free flap was 71.4% in our series. Bozikov and Arnez determined that free flap failure was 4.6 times more likely to occur after salvage free flap transfer, reporting a success rate of 53%.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Few scientific literatures proposed treatment about the surgical technique of reconstruction for this disease. There are a multitude of considerations and perioperative measures that aim to maximize the success of tissue transfer, including acknowledgment of psychological and psychiatric factors, tight glycemic control, nutritional support, intraoperative surgical technique, and close postoperative monitoring of the patients' hemodynamic physiology [ 87 ]. The defect resulted from radical surgical debridement is extensive, requiring reconstructive surgery with a pedicled than free flap.…”
Section: Discussionmentioning
confidence: 99%
“…The literature demonstrates success rates in excess of 95 per cent. 240,241 The early detection of and intervention for flap failure forms an important part of ensuring low failure rates.…”
Section: Care Of Patients After Microvascular Free-flap Surgerymentioning
confidence: 99%